Granulosa Cell Tumor Of The Ovary – An Incidental Finding During Caesarean Section – A Rare Case Report - Roy, J; Babu, AS (Kathmandu University Medical Journal, 2015)
Approximately one-fourth of the ovarian neoplasms and cysts are diagnosed incidentally during caesarean section. The possibility of borderline tumor or cancer should be considered although existence of ovarian malignancy in pregnancy is rare. We report a case of a rare solid malignant tumor of the ovary incidentally found during caesarean section. Intraoperatively, it was thought to be a variant of the common ovarian teratoma. Ovariectomy was done but histopathology revealed it to be granulosa cell tumor. The diagnosis changed the prognosis and future treatment plan drastically. Equipped with this knowledge physicians can be made aware of the existence of this little-known ovarian neoplasm along with its rare association with pregnancy. Also one can better manage, counsel and follow-up the patients after delivery, given the knowledge of the tumours’ inevitable malignant potential and its high incidence of recurrence. Kathmandu University Medical Journal Vol.12(1) 2014: 60-63